Case Report of Fetal Macrosomia with Birth Weight 6.25 kg: A Rare Encounter - Maskey, Suvana; Gurung, Geeta (Journal of Institute of Medicine Nepal, 2021)
Newborn weight exceeding 4000 g or 4500 g is considered as macrosomia, incidence of which varies from 6 to 10% of all deliveries. Maternal diabetes, obesity, age >35 years, male baby, history of previous macrosomia, multiparity are few risk factors. It is associated with several maternal and neonatal complications and presents an obstetric challenge as there is no consensus regarding the most appropriate route of delivery for macrosomic baby. We report a rare case of fetal macrosomia with birth weight of 6.25 kg delivered by cesarean section to 39 years old woman at 38 weeks 6 days period of gestation.